Novel cycloviruses identified by mining human blood metagenomic data show close relationship to those from animals - Wang, Yuanqing; Jiang, Xiaojie; Xi, Yuan; Wei, Siqi; Ning, Songyi; Zhang, Wen (Frontiers in Microbiology, 2025)
The family Circoviridae includes the genera Circovirus and Cyclovirus. Cycloviruses have been found in serum samples from chronic HBV, HCV, or HIV-infected individuals as well as asymptomatic blood donors. However, research on cycloviruses is relatively limited. We used viral metagenomics to mine, analyze, and visualize the human blood virome, successfully identifying three new genomes, each encoding Rep and Capsid proteins. These proteins are crucial for viral replication and host-cell interaction: the Rep protein is involved in initiating viral genome replication, while the Capsid protein plays a key role in the assembly of new virions and the virus's ability to interact with host immune systems. Distance matrix and phylogenetic analyses show that these cycloviruses share high sequence similarity with viruses found in both humans and animals across different regions of Africa. This finding not only confirms the presence of previously uncharacterized cycloviruses in human blood, but also provides insight into their potential role in host transmission and their ecological significance. Further research is needed to explore the functional roles of these cycloviruses in viral pathogenesis, particularly how they may influence host immunity and contribute to chronic infections. Additionally, studies investigating the host range and mechanisms of cross-species transmission will be essential to understanding the broader implications of cycloviruses in human and animal health.